PROFIL KECANDUAN GAME DI SMPN 4 TAROGONG KIDUL KABUPATEN GARUT - Alit Tresna Yuansyah; Euis Eti Rohaeti; Tita Rosita (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2021)
This study aims to determine the online game addiction profile for classroom students VIII SMPN 4 Tarogong Kidul Kabupaten Garut. The sample involved was people, with data collection techniques using an online game addiction questionnaire. Based on descriptive quantitative data analysis techniques obtained research results as follows online game addiction profiles of students according to the medium category. Gender-based online games online games for male students are higher than the level of addiction to online games for female students. The results of online game addiction research in terms of indicators found that indicators of compulsion and tolerance in the high category while the withdrawal indicator depends on the medium category. Keywords: individual counseling, discipline.